Peculiarities of using informational operations by the international coalition during the Iraq military campaign in 2003 - Гетьманчук, Микола; Зазуляк, Зоряна; Hetmanchuk, Mykola; Zazuliak, Zoriana (Видавництво Львівської політехніки, 2019)
У статті досліджено форми, методи і засоби проведення інформаційних операцій на всіх етапах воєнної кампанії в Іраку 2003 р. силами міжнародної коаліції на чолі із США. Показано, що воєнна кампанія міжнародної коаліції в Іраку 2003 р. характеризувалася комплексним застосуванням спеціальних інформаційних операцій як у політичній, так і військовій сферах: 1) для повалення диктаторського режиму Саддама Хусейна в Іраку; 2) пошуку та знищення зброї масового ураження; 3) нейтралізації діяльності та ліквідації осередків терористичних організацій «Армії Магді», «Аль-Каїди землі Межиріччя» та інших; 4) надання допомоги іракському народові у розбудові демократичної держави. Практика воєнної кампанії в Іраку засвідчила, що сили міжнародної коаліції проводили інформаційні операції всіх видів: 1) для забезпечення та підтримки військових дій; 2) для дезінформації противника; 3) спеціальні; 4) в гуманітарній сфері. Спеціальними структурами військових контингентів країн коаліції реалізовувалися інформаційні операції переважно на оперативному та тактичному рівнях. Досвід воєнної кампанії В Іраку засвідчив, що спеціальні структури при проведенні інформаційних операцій враховували: а) контент (стабілізаційний чи дестабілізаційний); б) суспільні цінності (традиційні чи руйнівні); в) характер суспільства (авторитарний, демократичний).

The article analyzes the forms, methods and means of conducting informational operations at all stages of the Iraqi military campaign by the US-led international coalition in 2003. It is shown that the military campaign of the international coalition in Iraq of 2003 was characterized by the complex use of special informational operations in both political and military spheres: 1) overthrowing the dictatorial regime of Saddam Hussein in Iraq; 2) search and destruction of mass destruction weapons; 3) neutralization of activity and liquidation of the centers of the terrorist organizations «Army of Magdi», «Al – Qaeda» and others; 4) assisting the Iraqi people in building a democratic state. The practice of the military campaign in Iraq has shown that international coalition forces conducted informational operations of all kinds: 1) ones to ensure and support military operations; 2) ones to misinform the enemy; 3) special ones; 4) humanitarian ones. Special structures of the military contingents of the coalition carried out informational operations mainly at the operational and tactical levels. The experience of the military campaign in Iraq has shown that special ways of conducting informational operations have taken into account: a) content (stabilizing or destabilizing); b) social values (traditional or destructive); c) the nature of society (authoritarian, democratic).
Особливості проведення міжнародною коаліцією інформаційних операцій під час воєнної кампанії в Іраку у 2003 р.
Keywords: міжнародна коаліція; воєнна кампанія; Ірак; інформаційна війна; інформаційна операція; інформаційна зброя; тероризм; international coalition; military campaign; Iraq; informational war; informational operation; informational weapon; terrorism; 327.51